Phytochemical and Pharmacological investigations on Boswellia serrata - Sharma, A.; Chhikara, S.; Ghodekar, S. N.; Bhatia, S.; Kharya, M. D.; Gajbhiye, V.; Mann, A. S.; Namdeo, A.G.; Mahadik, K. R. (Pharmacognosy Reviews)
Salai guggal is an oleo-gum-resin obtained from Boswellia serrata. Its essential oil is a mixture of mono, di and sesquiterpenes while gum fraction composed of pentose and hexose sugar with some digestive enzymes. Resin is the most important fraction of Salai guggal comprising mainly of pentacyclic triterpenic acids namely Boswellic acids. The therapeutic value of Salai guggal predominantly resides in its oleo-resin portion, which possess anti-inflammatory, anti-arthritic, anti-rheumatic, anti-diarrhoeal, anti-hyperlipidemic, anti-asthmatic, anti-cancer, anti-microbial and analgesic activity. In addition it has hepatoprotective and immunomodulatory activity as well. Boswellic acids are novel, specific, non-redox inhibitor of 5-lipoxygenase, an enzyme involved in arachidonic acid metabolism. This review focuses on the current state of therapeutic potential and phytochemical profile of Boswellia serrata.
Keywords: Apoptosis; Boswellia serrata; Boswellic acids; Inflammation; Leukotriene synthesis; 5-lipoxygenase